Efforts to Improve Early Mathematics Skills Through Smart Puzzle Among Children in Group A - Siti Ma Rifatul Munawaroh; Rina Syafrida; Ine Nirmala (S&Co Publishing, 2026)
Early mathematical skills are one of the fundamental abilities that should be developed from an early age. Initial observations in Group A at RA Al Hidayah Tegalwaru Karawang, revealed that children had difficulties in matching, comparing, grouping, sequencing, recognizing shapes and patterns, and identifying numbers and numeral symbols. This study aimed to improve these early mathematical skills through the use of the Smart Puzzle learning medium. The study employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 17 children aged 4-5 years in Group A at RA Al Hidayah Tegalwaru Karawang. Data were collected through observation sheets, developmental rubrics, performance assessments, and documentation, and analysed using descriptive quantitative and qualitative techniques. The findings showed that the average achievement of children’s early mathematical skills increased from 39,87% in the pre cycle to 54,97% in cycle I and 80,38% in cycle II. Classroom observations also indicated greater engagement, focus, and participation during learning. These findings suggest the Smart Puzzle can be used as an alternative learning medium to support the development of early mathematical skills in young children.